Purification and characterization of cellulase from Aspergillus unguis isolated from decaying coconut wood - Mohanappriya, S.; Kapilan, R. (AGRIEAST 2021 Vol.15 (1): 14-27, 2021)
The insufficiency of available natural fossil fuels for increasing human population, air pollution due to partial combustion of fossil fuel and the release of greenhouse gasses have led great attention on the usage of cellulase like enzymes to hydrolyze lignocellulosic substances to produce bioethanol. Thermostability and kinetic properties of cellulases need to be studied before deciding the eligibility of the enzymes for their potential applications. This study was aimed to purify the crude cellulase from Aspergillus unguis and to characterize the purified cellulase. When the crude enzyme from Aspergillus unguis isolated from decaying coconut wood, was subjected to fractional precipitation and dialysis by the addition of 80% saturated (NH4)2SO4, the recovery of cellulase was 83.9 % showing specific activity of 16386.43Umg-1 protein. The dialyzed enzyme was added to a column packed with DEAE-Sepharose equilibrated with 0.01M sodium phosphate buffer (pH 7.0) and unbound proteins were washed with the same buffer. The specific activity of cellulase was increased from 3228 to 37071 Umg 1 protein, which was 11.5-fold higher than that of the crude cellulase with 67.6 % yield. The molecular weight of the purified cellulase was determined as 50 KDa using Poly Acrylamide Gel Electrophoresis (SDS-PAGE). When the activity of purified cellulase was measured at different temperatures ranging from 40oC to 90oC at neutral pH, the optimum temperature for the activity of the purified cellulase enzyme was 70oC. The pH was optimized as 5.0 for the cellulase at 70oC. Michaelis constant for the purified cellulase to soluble cellulose by Lineweaver-Burk Plot was 4.45 ×10-2 moldm-3 and Vmax was 28.5714 mgml-2mins-1 with 10 gL 1 of cellulose substrate, at pH 5.0 and 70oC. The purified cellulase was stable for at least 90 minutes at pH 5.0 and 70oC and the half-life obtained for this enzyme was significantly higher at 70oC than any other temperatures. Therefore, the crude cellulase from Aspergillus unguis can be purified by ammonium sulphate precipitation and DEAE-sepharose ion exchange chromatography. The thermostable acidic cellulase from Aspergillus unguis could be a potential candidate for diverse industrial applications.
Keywords: Aspergillus unguis; cellulase; Kinetic properties; Michaelis constant; purification